Combined management of resectable and locally advanced pancreatic cancer – is there an optimal therapeutic model? - Świeboda-Sadlej, Anna; Heleniak, Hubert (Contemporary Oncology/Współczesna Onkologia, 2008)
This article presents the current status, controversies, and future prospects for the treatment of resectable and locally advanced pancreatic cancer. When diagnosed, it is distinguished by bad outcome with death rate about 98% and median survival ranging from 3 to 6 months. The treatment of early stages includes complete tumour resection, but at the time of diagnosis only 20–30% of patients may be qualified for the operation. Even with surgery, the survival rate of such patients is poor. One of the methods potentially improving results is adjuvant treatment. Data provided by the ESPACE-1 and CONKO-001 trials suggest that postoperative chemoradiotherapy is not better than chemotherapy alone and that gemcitabine-based chemotherapy has a chance to become standard adjuvant treatment. There are promising results of combined chemo- and radiotherapy based on gemcitabine as well as chemotherapy alone as neoadjuvant chemotherapy, but it needs confirmation in randomized trials. The optimal approach to patients with locally advanced pancreatic carcinoma is not determined. Although not universally accepted, 5-fluorouracil-based chemoradiation is considered a standard treatment in many countries worldwide. There are multiple trials confirming the benefits from gemcitabine-based chemoradiation, but due to the high toxicity this therapeutic option is reserved for patients in good general condition. Recent strategies for improving the efficacy of chemoradiotherapy include the use of new radiation techniques such as intensity-modulated radiation therapy (IMRT), stereotactic radiotherapy or combination of new molecular targeted agents with chemoradiotherapy. Many phase III trials evaluating systemic therapy have included not only metastatic but also locally advanced patients; therefore conclusions regarding chemotherapy and gemcitabine combined with erlotinib apply also to this second group.